Hypervariable 3' UTR region of plant LTR-retrotransposons as a source of novel satellite repeats - Macas, Jirí; Koblízková, Andrea; Navrátilová, Alice; Neumann, Pavel (Gene, 2009)
The repetitive sequence PisTR-A has an unusual organization in the pea (Pisum sativum) genome, being present both as short dispersed repeats as well as long arrays of tandemly arranged satellite DNA. Cloning, sequencing and FISH analysis of both PisTR-A variants revealed that the former occurs in the genome embedded within the sequence of Ty3/gypsy-like Ogre elements, whereas the latter forms homogenized arrays of satellite repeats at several genomic loci. The Ogre elements carry the PisTR-A sequences in their 3' untranslated region (UTR) separating the gag-pol region from the 3' LTR. This region was found to be highly variable among pea Ogre elements, and includes a number of other tandem repeats along with or instead of PisTR-A. Bioinformatic analysis of LTR-retrotransposons mined from available plant genomic sequence data revealed that the frequent occurrence of variable tandem repeats within 3' UTRs is a typical feature of the Tat lineage of plant retrotransposons. Comparison of these repeats to known plant satellite sequences uncovered two other instances of satellites with sequence similarity to a Tat-like retrotransposon 3' UTR regions. These observations suggest that some retrotransposons may significantly contribute to satellite DNA evolution by generating a library of short repeat arrays that can subsequently be dispersed through the genome and eventually further amplified and homogenized into novel satellite repeats.
Keywords: Phylogeny; Cloning, Molecular; genom rostlinný; satelitní DNA; genetická variace; Gene Amplification; amplifikace genu; Terminal Repeat Sequences; Genome, Plant; hrách setý; retroelementy; Genes, Plant; koncové repetice; rostlinné geny; Genetic Variation; 3' nepřekládaná oblast; DNA, Satellite; Pisum sativum; klonování DNA; fylogeneze; Retroelements; 3' Untranslated Regions